2020
DOI: 10.1136/bmjgh-2020-003362
|View full text |Cite
|
Sign up to set email alerts
|

Is time running out? The urgent need for appropriate global health curricula in Germany

Abstract: Recently, representatives of politics, health officials and academia in Germany have advocated a greater role for Germany in matters concerning global health. However, health professionals in Germany are rarely taught about global health topics and accordingly real expertise in this field is lacking. To advance knowledge and competencies at German universities and adequately equip health professionals to achieve Germany’s political goals, global health curricula must be developed at medical schools and other i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…10,37-41 Bozorgmehr 18,38 introduced an analytical framework for global health education, which expands on the social determinants of health. Most recently, Schuster et al 9 suggested a framework which is based on a Canadian model comprising five major dimensions: security, technical, entrepreneurial, humanitarian and social justice approaches. 42 This framework informed the development of global health programmes in medical education at Charité University Berlin.…”
Section: Where Are We Now? Discourse Strategies and Regulatory Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…10,37-41 Bozorgmehr 18,38 introduced an analytical framework for global health education, which expands on the social determinants of health. Most recently, Schuster et al 9 suggested a framework which is based on a Canadian model comprising five major dimensions: security, technical, entrepreneurial, humanitarian and social justice approaches. 42 This framework informed the development of global health programmes in medical education at Charité University Berlin.…”
Section: Where Are We Now? Discourse Strategies and Regulatory Frameworkmentioning
confidence: 99%
“…42 This framework informed the development of global health programmes in medical education at Charité University Berlin. 9 It is important to note that most complex suggestions for strengthening global health in medical education have been introduced, at first and foremost, by the national medical student association and their various representatives over time. [11][12][13]17,18,27,28,[43][44][45][46] These authors have identified a wide range of topics and challenges relevant to global health education, including a health systems approach and the social determinants of health, among others.…”
Section: Where Are We Now? Discourse Strategies and Regulatory Frameworkmentioning
confidence: 99%
See 3 more Smart Citations